KONTRIBUSI DAYA LEDAK OTOT TUNGKAI DAN KELENTUKAN TERHADAP AKURASI SHOOTING ATLET SSB TUNAS HARAPAN - Candra, Juli; Natas Pasaribu, Ahmad Muchlisin (UNIVERSITAS NEGERI MAKASSAR, 2020)
The problem in this research is the low level of accuracy shooting athletes football SSB Tunas Harapan Lubuk Basung, and suspected this problem arises disebebkan by several factors such as low level of explosive muscle leg muscle and the ability to shooting accuracy. This study aims to reveal the contribution of explosive muscle limb muscle strength and the accuracy of football shooting athletes SSB Tunas Harapan Lubuk Basung.This study included into correlational research. The population in this study is all athletes SSB Tunas Harapan Lubuk Basung which amounted to 170 people belonging to the category of age 10-14 th, 15-18 years and age 18 th and above. However, the athletes who were samples in this study were athletes with age category 15-18 years, and the sample data obtained amounted to 32 samples. From the results of research show that the correlation coefficient rtitung> rtabel (hypothesis accepted) and significant test coefficient variables X1 - Y, X2 - Y and X1 X2 to Y obtained Fcount> Ftabel. From the results of this study prove: (1) there is contribution between variable explosive muscle limb X1 to shooting accuracy (Y) of 52,7%. (2) there is contribution between variable kelentukan (X2) to shooting accuracy (Y) equal to 30,1%. (3) the contribution of explosive muscle limb power (X1) and the elasticity (X2) to shooting accuracy (Y) is 68,7%.